Antioxidant radical scavenging capacity and total carotenoid content of narrow-clawed crayfish (Pontastacus leptodactylus, Eschscholtz, 1823) in Atikhisar Reservoir (Çanakkale, Türkiye) - Acarlı Sefa; Kızılkaya Bayram; Vural Pervin; Berber Selçuk; Kale Semih; Acarlı Deniz (Oceanological and Hydrobiological Studies)
In this study, antioxidant radical scavenging capacity and total carotenoid content in the meat and shells of Pontastacus leptodactylus were investigated. Concerning the antioxidant scavenging effect, the highest IC50 values were found to be 388.77 mg g-1 and 155.53 mg g-1 for females and males in July and March, respectively. The mean IC50 values of the meat were calculated as 239.83 mg g-1 and 105.21 mg g-1 for females and males, respectively. The mean total carotenoid content in the meat was found to be 14.35 and 12.78 μg g-1 for females and males, respectively. The results indicated that crayfish meat had antioxidant radical scavenging capacity and was rich in carotenoid content.